Insulin-treated 3T3-L1 adipocytes and cell-free extracts derived from them incorporate 32P into ribosomal protein S6. - Smith, C J (1980)
Differentiated 3T3-L1 preadipocytes preincubated for 60 min with 32Pi incorporate 32P into ribosomal protein S6 within 5 min after exposure to 0.1-1.0 nM insulin. Undifferentiated 3T3-L1 cells, which possess only 3-5% of the high-affinity cell surface insulin receptors present on the differentiated cells, are less sensitive to this stimulation. Under the same conditions used for insulin, epidermal growth factor, antibody to the insulin receptor, and a combination of isoproterenol and 1-methyl-3-isobutylxanthine also promote 32P incorporation into S6 in the differentiated cells although less effectively than insulin. Cell-free extracts derived from cells treated for 5-10 min with either physiological concentrations of insulin or epidermal growth factor (0.1 microgram/ml) reflect intact cells and catalyze the incorporation of 32P from exogenous [gamma-32P]ATP into ribosomal protein S6.